2014
DOI: 10.2500/aap.2014.35.3749
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Toll-like receptors 2 and 9 and Th1/Th2 cytokines profile in obese asthmatic children

Abstract: Asthma is a common pulmonary disease with chronic inflammation of the airways, and obesity is a chronic state of low-grade inflammation. Toll-like receptors (TLRs) are involved in the innate immune response. This study was designed to analyze whether obesity has an effect on the immune response of patients with asthma. We included obese asthmatic, obese, asthmatic, and healthy children. Biochemical and anthropometric analyses were performed. Interleukin (IL)-2, interferon (IFN) gamma, IL-4, IL-10, IL-1beta, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Synthetic TLR9 ligands (CpG ODNs) are shown to be beneficial in various animal models of asthma and even in a number of early human clinical trials , while CpG ODNs are also reported to activate TLR9 and cause lung inflammation . In fact, consistent with our previous report and the study of Carmen Maldonado‐Berna that high expression of TLR9 is found in asthma , the present study demonstrated that pronounced elevated expression of TLR9 was accompanying with lung inflammation exacerbation in WT mice after OVA challenges. However, such OVA‐induced inflammation including inflammatory cells around bronchial, mucus production in the airways, IgE level in the plasma, total and differential inflammatory cell infiltration in the BALF, and pro‐inflammatory cytokine production such as IL‐4 and IL‐13 was significantly attenuated in OVA‐challenged TLR9 −/− mice.…”
Section: Discussionsupporting
confidence: 91%
“…Synthetic TLR9 ligands (CpG ODNs) are shown to be beneficial in various animal models of asthma and even in a number of early human clinical trials , while CpG ODNs are also reported to activate TLR9 and cause lung inflammation . In fact, consistent with our previous report and the study of Carmen Maldonado‐Berna that high expression of TLR9 is found in asthma , the present study demonstrated that pronounced elevated expression of TLR9 was accompanying with lung inflammation exacerbation in WT mice after OVA challenges. However, such OVA‐induced inflammation including inflammatory cells around bronchial, mucus production in the airways, IgE level in the plasma, total and differential inflammatory cell infiltration in the BALF, and pro‐inflammatory cytokine production such as IL‐4 and IL‐13 was significantly attenuated in OVA‐challenged TLR9 −/− mice.…”
Section: Discussionsupporting
confidence: 91%
“…However, IL-4 and IFNγ production by T lymphocytes after mitogen stimulation was reduced in obese patients compared with controls. Our findings were in agreement with a previous study that showed a decrease in cytokine secretion in obese patients [47] [48]. The INFγ/IL-4 ratio was unchanged in obese patients, reflecting no change in the profile of Th1/Th2 lymphocytes.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have suggested a mechanistic correlation between JNK signaling pathway and TLR9 (Tsai et al, 2012;Holley et al, 2012;Mitchell and Olive, 2010), and the levels of TLR9 are indeed higher in obese asthmatic patients (Sanchez-Zauco et al, 2014). TLRs are abundant on various innate immune cells involved in asthma pathogenesis, including eosinophils, mast cells, plasmacytoid DCs and epithelial cells (Sanchez-Zauco et al, 2014). When pathogens or allergens entering the airway, they may be recognized by the expressed TLRs of these cells, which triggers the activation of TLRs downstream signaling to induce defense action via initiating cytokines secretion (Lin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%